DIMENSI PERSEPSI KEPUASAN PELAYANAN DRIVER GOJEK DALAM PERSPEKTIF ‘BRANDING STRATEGY’ - Ahmad Toni (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2018)
This reaserch aims to know the perception of custumer satisfaction in the service of Gojek drivers in Jakarta. The population in this study arethe consumers who use the Ministry of Transportation online. Using sampling techniques in dept interview to the informant that add up to 3 people with their ages and different professions. Analysis technique used is a used qualitative descriptive method to provide facts and data. The result of the perception of customer satisfaction in the service of Gojek drivers in Jakarta was positive. Service driver Gojek proven can affect customer satisfaction. Duw to transportation online community services to perform, then starting from the performance nor the transport attribute can affect the perception of the customers. Good or bad perceptions that exist in the community against the online transportation, depending on the quality of the service itself. The succes of a services in the field of services support by the performance drivers of transportation online at the time or providing service to customers. Services provided to the community will greatly influnece public perception as well as a good perception towards transportation online.